2019
DOI: 10.1080/13645579.2019.1672281
|View full text |Cite
|
Sign up to set email alerts
|

Using creative methods to research across difference. An introduction to the special issue

Abstract: This special issue explores some of the methodological challenges that are brought into play when scholars deploy creative methods to research across difference. Within the research methods literature, the term 'creative methods' is typically used to refer to an approach that enables people to express themselves in non-verbal ways (Gauntlett, 2007), often used in combination with more traditional methods such as interviews and focus groups. Mannay (2016) (drawing on Pauwels, 2011) suggests that creative method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…Art-based qualitative methods have gained ground in related research areas, such as education, in which they have proven to be vital in gaining insights that more widespread methods, such as surveys and interviews, struggle to capture (Brooks et al, 2020). Based on a systematic literature review, we showed how art-based research methods have gained limited ground within science education research with a few identified studies.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 98%
See 1 more Smart Citation
“…Art-based qualitative methods have gained ground in related research areas, such as education, in which they have proven to be vital in gaining insights that more widespread methods, such as surveys and interviews, struggle to capture (Brooks et al, 2020). Based on a systematic literature review, we showed how art-based research methods have gained limited ground within science education research with a few identified studies.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 98%
“…It is worth paying attention to these various elements that extend beyond oral and written language because they challenge the barriers and constraints related to language skills, such as cognitive abilities and native language (Polkinghorne, 2005). The vulnerability of language requires the abilities to recognize, remember, and pronounce with confidence when speaking and writing (Brooks et al, 2020). Such challenges are overcome by utilizing the potential of art-based methods to move beyond language skills and barriers by expressing wordless understandings of the world.…”
Section: Non-verbal Languagementioning
confidence: 99%
“…From the creative procedure in this characteristic, this was considered as the response of the physiology (Aniago, E., et al, 2020;Weisberg, R. W., 2004), including creating the co-learning from the new developed environment (Braun, V. & Clark, V., 2006;Anderson, R. C. & Haney, M., 2020;Brooks, R., et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The present study is based on a multi-method approach, where researchers are interested in beliefs, percentages, experiences and systems of meaning. The mixed or multi-method research includes statistical analysis and empirical calculation according to Brooks, Lainio, and Lažetić (2020). In this way, the roots of qualitative research are found in social and cultural anthropological, philosophical, psychological, historical and sociological research, contemplating a theoretical-legal documentary type design (Corona et al, 2017).…”
Section: Methodsmentioning
confidence: 99%